Chitosan-catechol: a writable bioink under serum culture media. (18th April 2018) - Lee, Daiheon; Park, Joseph P.; Koh, Mi-Young; Kim, Pureum; Lee, Junhee; Shin, Mikyung; Lee, Haeshin
Abstract : Mussel-inspired adhesive polymers exhibiting rapid complexation with serum proteins are used as a direct writable bioink for additive techniques, 3D printing. The mussel-inspired bioinks would be a promising way to design a biocompatible 3D bioink cross-linked without any external stimuli. Abstract : Mussel-inspired adhesive coatings on biomedical devices have attracted significant interest due to their unique properties such as substrate independency and high efficiency. The key molecules for mussel-inspired adhesive coatings are catechol and amine groups. Along with the understanding of catechol chemistry, chitosan-catechol has also been developed as a representative mussel-inpired adhesive polymer that contains catechol and amine groups for adhesiveness. Herein, we demonstrated the direct writability of chitosan-catechol as a bioink for 3D printing, one of the additive techniques. The use of chitosan-catechol bioink results in the formation of 3D constructs in normal culture media via rapid complexation of this bioink with serum proteins; in addition, the metal/catechol combination containing tiny amounts of vanadyl ions, in which the ratio of metal to catechol is 0.0005, dramatically enhances the mechanical strength and printability of the cell-encapsulated inks, showing a cell viability of approximately 90%. These findings for mussel-inspired bioinks will be a promising way to design a biocompatible 3D bioink cross-linked without any external stimuli.